Investigating the roles of Gfi1/1b transcription factors, Lsd1 histone demethylase and long non coding RNA 1/2 genes in haematopoiesis during zebrafish embryogenesis - Khalaf, Samer Naji (2024)
Cellular differentiation entails the activation of mature cell markers and the repression of genes that are characteristic for immature cell states and alternative differentiation paths. Their repression involves transcriptional repressors and numerous non-coding RNAs that act to suppress gene expression at a transcriptional and post-transcriptional level. During zebrafish embryogenesis, two long ncRNAs, si:ch211-114p16.1 and si:ch211-114p16.2, as well as members of the Gfi1/1b repressor family and their interaction partner and co-repressor Lsd1/Kdm1a are expressed during blood cell differentiation from the lateral mesoderm. Here, I show that while the long ncRNAs are useful lineage markers they are neither required for haematopoiesis nor needed for the survival of the zebrafish. The zebrafish genome encodes two orthologues of mouse Gfi1, Gfi1aa and Gfi1ab, in addition to a single orthologue of the mouse Gfi1b protein. Just like mouse Gfi1/1b double mutant embryos, zebrafish gfi1aa/1ab/1b triple mutant embryos are anaemic at the time when primitive red blood cells (prRBCs) populate the circulation of a wildtype embryo. Here, to find out more about the fate of the mesodermal prRBC progenitors I have performed a single cell RNA-sequencing experiment. To increase the number of embryos available for this experiment, I used the latest CRISPR/Cas9 technology to establish generation zero (G0) triple mutant embryos. These faithfully phenocopied the prRBC defect of the stable triple mutants. For the scRNA-seq experiment, the blood progenitors of interest were sorted from embryos that carried two reporter transgenes, qmc551:GFP and gata1:dsRed. The transcriptomic data on the GFP and dsRed single and double positive cells demonstrates a complete loss of mature prRBCs, as well as a severe reduction in the number of haematopoietic progenitors among the sorted G0 triple mutant cells. It also shows a concomitant increase in neutrophil granulocytes. These data xix highlight the important roles that Gfi1/1b proteins play in haematopoietic progenitor maintenance and mesodermal progenitor cell commitment to the prRBC lineage. Interestingly, loss of the Gfi1/1b interaction partner Lsd1/Kdm1a does not lead to severe anaemia in either stable or G0 mutant embryos. The latter were generated as part of this project. They will serve as a valuable source for Lsd1/Kdm1a mutant cells for future single cell RNA-sequencing experiments in which to explore the differential need for Gfi1aa/1ab/1b and Lsd1/Kdm1a in mesodermal prRBC progenitors.